2010
DOI: 10.1016/j.jeurceramsoc.2010.01.038
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of recycled paper processing residues and clay of different sources for the production of porous anorthite ceramics

Abstract: Production of porous anorthite ceramics from mixtures of paper processing residues and three different clays are investigated. Suitability of three different clays such as enriched clay, commercial clay and fireclay for manufacturing of anorthite based lightweight refractory bricks was studied. Porous character to the ceramic was provided by addition of paper processing residues (PPR). Samples with 30-40 wt% PPR fired at 1200-1400• C contained anorthite (CaO·Al 2 O 3 ·2SiO 2 ) as major phase and some minor sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
67
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(69 citation statements)
references
References 13 publications
2
67
0
Order By: Relevance
“…previous study of the authors [15]. This was because the sawdust addition was expected to supply additional heat to the sample during firing and hence samples may warp due to premature melting.…”
Section: Methodsmentioning
confidence: 91%
See 3 more Smart Citations
“…previous study of the authors [15]. This was because the sawdust addition was expected to supply additional heat to the sample during firing and hence samples may warp due to premature melting.…”
Section: Methodsmentioning
confidence: 91%
“…In order to increase the amount of porosity in the samples, wooden sawdust with particle size smaller than 3 mm was used as burnout pore-making additive as well as the paper waste. The mixtures containing clay and 30 wt% paper waste (on dry basis) that supplied the strongest anorthite composition [15] were prepared for production of the samples. Recycled paper processing waste was in sludge form.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies [23,24] have confirmed that the presence of anorthite increases the strength and chemical stability of the material and improves its physical properties such as low thermal expansion coefficient, high thermal shock resistance, and low dielectric constant. Actually, porous anorthite ceramics with high compressive strength are obtained from mixtures of paper processing residues and clays [25]. Anorthite based ceramics with an important dielectric resistance were also prepared from kaolin DD2 and calcite [26].…”
Section: Materiais Cerâmicos Porosos De Mulita-anortita-albita Foram mentioning
confidence: 99%